IMPLEMENTATION OF PROJECT BASED LEARNING ASSISTED BY STUDENTS’ WORKSHEET: FOSTERING STUDENTS’ CREATIVE THINKING SKILLS IN SCIENCE LEARNING - Hayati, Dwi Siti Nur; Rahman, Rini Yunita; Hidayatussaadah, Rulis; Nurohman, Sabar; Winarto, Winarto (Universitas Bhinneka PGRI, 2026)
Science learning ideally fosters thinking skills. Creative thinking is one of the skills that needs to be developed in students to address the complex challenges of modern times. This study aims to develop creative thinking skills through the implementation of Project-based Learning (PjBL) assisted by student’s worksheet in science learning on the topic of ecology. This is a quasi-experimental study with a one-group pretest-posttest design. Data analysis techniques used quantitative descriptive methods. The sample selection technique employed purposive sampling. The research sample consisted of 30 students from class VII B of SMP Negeri 1 Sleman, Yogyakarta. The results indicated that PjBL model assisted by students’ worksheet was sufficiently effective in fostering students' creative thinking skills. The average pretest score was 42.3, the posttest score was 74.2, and the average N-Gain was 0.56, categorized as medium. The percentage increase in the achievement of each critical thinking skill indicator based on the pretest and posttest results was as follows: fluency increased by 12%, flexibility by 35%, originality by 16%, and elaboration by 38%.